2015
DOI: 10.1007/s00198-015-3264-1
|View full text |Cite
|
Sign up to set email alerts
|

A 2-year prospective densitometric study on the influence of Fok-I gene polymorphism in young patients with thalassaemia major

Abstract: Our study indicates a protective role of the f allele of the Fok-I gene polymorphism when found in homozygosity on bone mineral density of young patients with b-TM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Another study indicated a significant role for VDR polymorphisms ( BsmI / ApaI / TaqI haplotype) in the susceptibility of childhood epilepsy which is highly associated with vitamin D deficiency [50]. In thalassemic patients, it was reported that FokI [51] and BsmI polymorphisms influence vitamin D levels [52]. In a study by Ragia et al [53], the CC genotype of FokI (corresponding to the FF genotype) was associated with the lowest concentration of vitamin D in patients with obstructive sleep apnea syndrome, compared to those bearing the CT (Ff) or TT (ff) genotype, and the interaction of vitamin D with VDR FokI polymorphism was significantly associated with obstructive sleep apnea syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated a significant role for VDR polymorphisms ( BsmI / ApaI / TaqI haplotype) in the susceptibility of childhood epilepsy which is highly associated with vitamin D deficiency [50]. In thalassemic patients, it was reported that FokI [51] and BsmI polymorphisms influence vitamin D levels [52]. In a study by Ragia et al [53], the CC genotype of FokI (corresponding to the FF genotype) was associated with the lowest concentration of vitamin D in patients with obstructive sleep apnea syndrome, compared to those bearing the CT (Ff) or TT (ff) genotype, and the interaction of vitamin D with VDR FokI polymorphism was significantly associated with obstructive sleep apnea syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In our thalassemic population, we found that VDR (FokI, BsmI) and COL1A1 (Sp1) gene polymorphisms had no influence on BMD, but BsmI was found to display beneficial effects on patient response to alendronate therapy (76). It has recently been reported that the f allele of the Fok-I gene polymorphism, when found in homozygosity, confers protection on the BMD values of young thalassemic patients (77).…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Moreover, after controlling for age, weight, and hypogonadism, vitamin D is a strong predictor of spine BMD . Recent observations suggest that thalassemia patients who carry Fok‐1 ff type polymorphisms have increased hip BMD . Despite these strong associations, to date there have been no published vitamin D interventional trials where bone density or fracture have been primary outcomes.…”
Section: Low Bone Massmentioning
confidence: 99%